The impact of melatonin on the sleep patterns of women undergoing IVF: a double blind RCT. Issue 4 (6th January 2018) - Fernando, Shavi; Biggs, Sarah Nichole; Horne, Rosemary Sylvia Claire; Vollenhoven, Beverley; Lolatgis, Nicholas; Hope, Nicole; Wong, Melissa; Lawrence, Mark; Lawrence, Anthony; Russell, Chris; Leong, Kenneth; Thomas, Philip; et al.
Abstract: STUDY QUESTION: Does melatonin result in a dose–response effect on sleep quality and daytime sleepiness in women undergoing IVF? SUMMARY ANSWER: Melatonin, even when given at high doses twice per day, does not cause significant daytime sleepiness or change night time sleep quantity or quality. WHAT IS KNOWN ALREADY: Melatonin is being increasingly used as an adjuvant therapy for women undergoing IVF owing to its antioxidative effects. It is widely considered to be sedative but there are scant objective data on the effects of melatonin on sleep in the setting of IVF. STUDY DESIGN SIZE, DURATION: The study was a double-blind placebo-controlled randomized trial of 116 women recruited between September 2014 and September 2016. PARTICIPANTS/MATERIALS, SETTING, METHOD: Women who were undergoing their first cycle of IVF at private IVF centers were recruited into the RCT and randomized to receive either placebo, 2 mg, 4 mg or 8 mg of melatonin, twice per day (BD) from Day 2 of their cycle until the day before oocyte retrieval. Each participant wore an accelerometer that provides an estimate of sleep and wake activity for up to 1 week of baseline and throughout treatment (up to 2 weeks). They also kept sleep diaries and completed a Karolinska sleepiness score detailing their night time sleep activity and daytime sleepiness, respectively. MAIN RESULTS AND THE ROLE OF CHANCE: In total, 116 women were included in the intention-to-treat analysis (placebo BD ( n = 32), melatonin 2 mg BD ( n = 29), melatonin 4 mg BD ( n = 26), melatonin 8 mg BD ( n = 29)). There were no significant differences in daytime Karolinska sleepiness score between groups ( P = 0.4), nor was there a significant dose–response trend (β=0.05, 95% CI −0.22–0.31, P = 0.7). There were no differences in objective measures of sleep quantity or quality, including wake after sleep onset time, sleep onset latency, and sleep efficiency before and after treatment or between groups. There was an improvement in subjective sleep quality scores from baseline to during treatment in all groups, except 8 mg BD melatonin: placebo (percentage change −13.3%, P = 0.01), 2 mg (−14.1%, P = 0.03), 4 mg (−8.6%, P = 0.01) and 8 mg (−7.8%, P = 0.07). LIMITATIONS, REASONS FOR CAUTION: As this was a subset of a larger trial, the melatonin in ART (MIART) trial, it is possible that the sample size was too small to detect statistically significant differences between the groups. WIDER IMPLICATIONS OF THE FINDINGS: While this study suggests that melatonin can be used twice per day at high doses to achieve sustained antioxidation effects, with the reassurance that this will not negatively impact daytime sleepiness or night time sleep habits, the sample size is small and may have missed a clinically significant difference. Nevertheless, our findings may have implications not only for future studies of fertility treatments (including meta-analyses), but also in other medical fields where sustained antioxidation is desired. STUDY FUNDING/COMPETING INTERESTS: This study was funded by the Monash IVF Research and Education Foundation (PY12_15). S.F. is supported by the National Health and Medical Research Council (Postgraduate Scholarship APP1074342) and the Royal Australian and New Zealand College of Obstetricians and Gynaecologists Ella Macknight Memorial Scholarship. E.W. is supported by an National Health and Medical Research Council Program Grant (APP1113902). S.F., E.W., R.H., B.V., N.L., N.H., M.W., M.L., A.L., P.T., K.L. have nothing to declare. L.R. is a Minority shareholder in Monash IVF Group, has unrestricted grants from MSD®, Merck-Serono® and Ferring® and receives consulting fees from Ferring®. S.N.B. reports consulting fees from Johnson & Johnson Consumer Inc®, outside the submitted work. TRIAL REGISTRATION NUMBER: This trial was prospectively registered with the Australian New Zealand Clinical Trials Registry (Project ID: ACTRN12613001317785). TRIAL REGISTRATION DATE: 27/11/2013 DATE OF FIRST PATIENT'S ENROLMENT: 1/9/2014